1998
DOI: 10.1128/jcm.36.7.2087-2088.1998
|View full text |Cite
|
Sign up to set email alerts
|

Coryneform Bacteria in Throat Cultures of Healthy Individuals

Abstract: Throat swabs from 113 healthy individuals from Hamburg, Germany, and Zurich, Switzerland, were investigated for coryneform bacteria with nonselective and selective media. Ninety specimens contained 123 strains. Surprisingly, 76% of them were strains ofCorynebacterium durum (47%) and Rothia dentocariosa (29%). Only two were strains ofCorynebacterium pseudodiphtheriticum, and none were strains of C. striatum, C. amycolatum, or C. diphtheriae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 15 publications
1
22
1
Order By: Relevance
“…This in turn suggests that asymptomatic carriage of C. diphtheriae is not uncommon, but C. diphtheriae throat carriage has been described to be rare or absent among patients with upper respiratory tract infections and asymptomatic individuals . However, these studies involved few socially/professionally active and healthy subjects and bacterial flora of the upper respiratory tract in infected patients may not be representative of that in the general population . Asymptomatic throat carriage may also concern only a particular sub‐population or may be transient, and cutaneous carriage has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This in turn suggests that asymptomatic carriage of C. diphtheriae is not uncommon, but C. diphtheriae throat carriage has been described to be rare or absent among patients with upper respiratory tract infections and asymptomatic individuals . However, these studies involved few socially/professionally active and healthy subjects and bacterial flora of the upper respiratory tract in infected patients may not be representative of that in the general population . Asymptomatic throat carriage may also concern only a particular sub‐population or may be transient, and cutaneous carriage has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…ST181 does not share any allele with other French C. diphtheriae belfanti. We compared the nucleotide sequences at each locus by NCBI blast, and the rpoB sequence was homologous to that of a C. diphtheriae belfanti isolate collected from the ear of a cat . The feline isolate carries the tox gene but does not express the diphtheria toxin.…”
Section: Discussionmentioning
confidence: 99%
“…This group of bacteria includes members of the genera Corynebacterium, Brevibacterium, Dermabacter, Microbacterium, Rothia, Turicella, Arthrobacter, and Oerskovia as well as several other genera. Coryneform bacteria are widely distributed in the environment as commensals colonizing the skin and mucous membranes of humans and other animals, [27][28][29] and are commonly considered contaminants without clinical significance. 30,31 However, the high percentage of coryneform bacteria isolates found in this study, and the presence of coryneform bacteria with other pathogenic bacteria in some cases, may allow reasonable challenge of this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…The current database lists 98% of all Rothia spp. as catalase positive, but a very recent study demonstrated that up to one-third of all Rothia strains are catalase negative (9). Other minor modifications of the RapID CB Plus database which seem to be necessary (Table 2) include the introduction of pyrrolidonyl aminopeptidase-positive Arcanobacterium pyogenes and Corynebacterium minutissimum strains, proline aminopeptidase-negative CDC group G and Oerskovia strains, and glycosidase-positive Rothia strains.…”
Section: Discussionmentioning
confidence: 99%